Factors Influencing Generation Z Tourists' Perceptions of Sustainable Bicycle Tourism in Phra Nakhon Si Ayutthaya Province - Srithong, Saranya; Duantrakoonsil, Tattawan; Kieanwatana, Komsit (Journal of Multidisciplinary Academic Research and Development (JMARD), 2025)
This research aimed to compare the differences in personal factors, categorized by gender and place of origin, on the tourist perception of sustainable bicycle tourism in Phra Nakhon Si Ayutthaya Province and to study the bicycle tourism components that influence perceptions of sustainable tourism management among Gen Z tourists. This quantitative study was conducted with 385 Thai Gen Z tourists who participated in bicycle tourism at the Ayutthaya Historical Park. The sample was selected using a convenient sampling method. The questionnaire used had a reliability coefficient (Cronbach’s alpha) of 0.956. Quantitative data were analyzed using frequency distribution, percentage, mean (), standard deviation, Pearson’s Product-Moment Correlation, One-Way Analysis of Variance (ANOVA or F-test), and multiple regression analysis via the Enter method. Independent variables included bicycle tourism components: tourism resources, accessibility, amenity, and complementary services. The dependent variable was the perception of sustainable bicycle tourism management, with statistical significance set at 0.05. The results revealed that personal factors, such as gender and place of origin, did not significantly influence the overall tourist perception of sustainable cycling tourism. The respondents’ opinions on bicycle tourism components were generally at a high level ( = 4.052, S.D. = 0.505). When considering specific components, the respondents exhibited high levels of agreement across all subcomponents. Among the bicycle tourism components, tourism resources and accessibility significantly influenced the perception of sustainable bicycle tourism management at the 0.05 level of significance. The tourism components influencing the tourist perception of sustainable bicycle tourism management, ranked by importance, were accessibility (Beta = 0.571), tourism resources (Beta = 0.327), and complementary services (Beta = 0.117).